(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: The objective of this study was to determine the antibacterial activity of spices against common pathogenic bacteria and Minimum Inhibitory Concentration (MIC) of spices extract. Methods: Dried buds of Syzygium aromaticum, bulb of Allium sativum, root of Allium sativum and rhizome of Curcuma longa were collected from different locality in Kathmand, Nepal. They were dried, crushed to powder form and mixed with adequate ethanol and methanol to get the extract respectively. After processing, the extracts were tested against Bacillus spp, Klebsiella pneumoniae, S. aureus and Escherichia coli by disc diffusion on Muellar Hinton Agar plate. Minimum Inhibitory Concentration (MIC) was determined by dilution technique. Results: All the extract of spices were found effective against Bacillus spp, K. pneumoniae, S. aureus and E. coli. However, the ethanolic extract of clove was found to be highly effective against E. coli with Zone of Inhibition (ZOI) of 28 mm. Similarly, the methanolic extract of clove was found to be highly effective against K. pneumoniae (ZOI= 22 mm). The MIC against S. aureus, Bacillus spp, K. pneumoniae and E. coli, of the ethanolic extract of clove was found to be 1:32, 1:8, 1:4 and 1:16 and methanolic extract was found to be 1:64, 1:16, 1:8 and 1:4, respectively. Conclusion: Clove was found to be the most effective spice against common pathogenic bacteria. Ehanolic extract was found to be more effective compared to methanolic suggesting ethanol as a suitable solvent. Further study on its antibacterial characteristics may be required to update its medicinal value.